SEVERE REFRACTORY HYPERCALCEMIA DUE TO ECTOPIC PARATHYROID LEADING TO MORTALITY - Woon, Loi Wee; Esha, Shaleela Mohd; Jalal, Fadzliana Hanum (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypercalcemia can manifest in a nonspecific manner, with vague symptoms which can be easily missed. Most cases of severe hypercalcemia are due to primary hyperparathyroidism or malignancy-related hypercalcemia, which is discernible by parathyroid hormone levels. We describe a case of severe refractory hypercalcemia attributed to ectopic parathyroid, which led to multiple morbidities and eventually mortality. CASE A 61-year-old male, with known hypertension and chronic kidney disease Stage III, presented with abdominal discomfort, loss of appetite, nausea and vomiting for 2 weeks duration. On examination, he was dehydrated, obese and hypertensive. Laboratory investigations showed markedly raised serum corrected calcium level of 5.17 mmol/L, low serum phosphate 0.63 mmol/L and iPTH of 35.39 pmol/L [NR 1.95-8.49]. Other investigations: Hb 15.6 g/dL, creatinine 303 umol/L, eGFR 18 ml/min/1.73 m2 and urea 5.7 mmol/L. Tumour markers CA 19-9, CA 125, AFP and CEA were normal. Paraneoplastic markers were negative. Neck ultrasound did not reveal any parathyroid lesion however, computed topography of the neck-thoraxabdomen-pelvis, revealed a well-defined hypodense soft tissue lesion at the superior mediastinum, inferior to the left inferior thyroid border, measuring 2.1 x 2.6 x 3.6 cm which may represent an ectopic parathyroid gland. Severe refractory hypercalcemia was treated with vigorous intravenous saline hydration, subcutaneous calcitonin, intravenous bisphosphonates and subcutaneous denosumab. His admission was prolonged and complicated with septicaemia requiring intubation and intensive care. The patient passed away after three weeks of admission. CONCLUSION This case demonstrates that severe and refractory hypercalcemia attributed to an ectopic parathyroid lesion may present late due to vague initial symptoms. Admission due to severe hypercalcemia require multiple modalities of treatment, may be prolonged and carries a high risk of mortality before definitive treatment with parathyroidectomy